Efektifitas Penerapan Problem Based Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Sekolah Dasar - Adhitya Wisnumurti (IMAGE, 2021)
Purpose of the study is to demonstrate the effectiveness of implementing Problem Based Learning in improving students' problem solving ability through science learning. The type of this study is experimental research design with non - randomized quasi-experimental pretest - posttest control group design. Subjects of this study were 29 students of SDN Tambakaji 04 with the class IVB as experimental group and class IVA as the control group. Data collection techniques used are observations, interviews, and tests and analyzed with quantitative analysis techniques using in SPSS 16.The study results showed increased scores on the post-test and produce a value of Asymp. Sig. 0.018 less than the significance level ( α = 0.05 ) on the statistics counting. There was a significant increase on the student’s problem solving skills by implementing Problem Based Learning in science learning. Therefore, it is expected that teachers should teach science with the nature of the subject that is by introducing the natural phenomenon's problem around them.